Effects of prospective thinking on intertemporal choice: The role of familiarity. Issue 10 (28th July 2015) - Sasse, Laura K.; Peters, Jan; Büchel, Christian; Brassen, Stefanie
Abstract: Imagining future events while performing an intertemporal choice task can attenuate the devaluation of future rewards. Here, we investigated whether this effect and its neural basis depend on the degree of personal prior experience associated with the simulated future scenarios. Functional magnetic resonance imaging was combined with a modified intertemporal choice task in which the delayed options were either purely monetary, or linked with a social event. Subject‐specific events differed regarding familiarity, that is, meeting a close, familiar person or a celebrity in a café. In line with recent hypotheses on episodic construction, the simulation of future familiar and unfamiliar events equally attenuated delay discounting behavior in comparison with the control condition and both were imagined with similar richness. Imaging data, however, indicate that these results rely on differential neural activation patterns. The hippocampus was particularly involved in the simulation of unfamiliar future scenarios, probably reflecting enhanced construction processes when personal experience with similar past events is lacking. Consequently, functional coupling of the hippocampus with neural valuation signals in the anterior cingulate cortex predicted the subjective value only of rewards offered in the unfamiliar context. In contrast, valuation of rewards in a familiar context was predicted by activation in key nodes of emotional and autobiographical memory retrieval and dynamically modulated by frontal‐striatal connectivity. The present data emphasize that the mechanisms underlying neural valuation of prospective rewards largely depend on the pre‐experience with the context in which they are offered. Hum Brain Mapp 36:4210–4221, 2015 . © 2015 Wiley Periodicals, Inc.